Global Trends in Digital Islam Learning Research with Bibliometric Mapping - Biela, Jihan Salsa; Maksum, Muh. Nur Rochim; Salim, Hakimuddin; Andhim, Muk (Universitas Muhammadiyah Surakarta, 2023)
Today's educational landscape is dominated by media, with a shift away from traditional lecture-based teaching approaches and toward more hands-on, interactive learning through the use of learning media. Learning media play a crucial role, particularly in educational activities that prioritize competences associated with process skills. The importance of media in facilitating students (learners), its presentation is adjusted to the learning objectives set. The purpose of this study is to track the evolution and trajectory of digital learning research in Scopus-indexed articles. This research examined every article indexed in the Scopus database using bibliometric analytic tools of Global Trends in Digital Learning Research a Bibliometric Mapping from 2020 to 2024. Data analyzed using Excel and R/R-Studio. VOSviewer is used to perform visual analysis of the simultaneous occurrence of keywords and document citations. The authors found 2,154 publications that fit the function, subject, and criteria set. The results of this study show an annual growth rate of 9.26%, with publications on Global Trends in Digital Learning Research a Bibliometric Mapping the most in 2023. China became the country that contributed the most publications with affiliations from the Ministry of Education. Zhang Y became the most prolific writer on the theme of Education Learning. The scope of the bibliometric study was restricted to data from Scopus. The study did not account for other national and international databases. This study offers suggestions for further research by giving a succinct summary of the literature available to education and technology researchers.